2009
DOI: 10.17221/1738-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects on growth performance, faecal microflora and plasma cholesterol after supplementation of spray-dried metabolite to postweaning rats

Abstract: ABSTRACT:A study was conducted to study the effects of feeding a spray-dried metabolite (SDM) produced by Lb. plantarum I-UL4 in the diets of postweaning rats on growth performance, faecal pH, Enterobacteriaceae bacterial and lactic acid bacteria (LAB) counts in the faeces and on plasma cholesterol concentrations. A total of 15 female 4-weeks-old Sprague dawley rats were randomly assigned to 3 groups of diets: basal diet (control), 0.25% SDM and 0.5% SDM diets. Daily feed intake, daily growth rate, blood plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…This is complement with Loh et al (2009) when they reported that feeding 0.25% spray-dried metabolite was able to reduce the plasma cholesterol concentration in postweaning rats. Fermented milk containing L. acidophilus L1 had effects in reducing 2.4-3.2% of serum cholesterol concentration in human (Lee et al, 2009).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…This is complement with Loh et al (2009) when they reported that feeding 0.25% spray-dried metabolite was able to reduce the plasma cholesterol concentration in postweaning rats. Fermented milk containing L. acidophilus L1 had effects in reducing 2.4-3.2% of serum cholesterol concentration in human (Lee et al, 2009).…”
Section: Discussionsupporting
confidence: 55%
“…The cholesterol concentration was measured by enzymatic method using the cholesterol diagnostic kit (Randox Laboratories Ltd, UK). This procedure was based on the method as described by Loh et al (2009). The determination method of fatty acids was modified from Oliveira et al (2009).…”
Section: Animals and Dietsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total fatty acids were extracted from breast muscles based on the method Folch et al (1957), described by Loh et al (2009), and modified by Ebrahimi et al (2014), using chloroform : methanol (2 : 1, v/v) containing butylated hydrotoluene to prevent oxidation during sample preparation. The extracted fatty acids were transmethylated to their fatty acid methyl esters (FAME) using 0.66 N KOH in methanol and 14% methanolic boron trifluoride (BF 3 ) (Sigma Chemical Co., St. Louis, Mo, USA) according to the methods by AOAC (1990).…”
Section: Methodsmentioning
confidence: 99%